(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The substantiation (is conducted on the basis of the data of X-ray analysis) good separability of a slag crust during a welding at attachment in a blend of a powder strand of zirconium dioxide.